The impact of IGRA positivity in untreated inactive pulmonary tuberculosis on IVF-ET outcomes in infertile women: an ambispective cohort study - Gai, Xiaoyan; Chi, Hongbin; Zeng, Lin; Chen, Lixue; Sheng, Zikang; Cao, Wenli; Zhang, Chen; Qu, Jingge; Zhang, Yue; Zhang, Weixia; Zhou, Qingtao; Liu, Ping; et al. (Frontiers in Medicine, 2025)
BackgroundTuberculosis can negatively impact both overall health and female reproductive function. This study investigated the relationship between the interferon-gamma release assay (IGRA) status and pregnancy outcomes in infertile women, with untreated “inactive” tuberculosis lesions observed on chest radiography, who are undergoing in vitro fertilization and embryo transfer (IVF-ET).MethodsThis ambispective cohort study, which includes retrospective (2012–2019) and prospective (2020–2024) cohorts, enrolled infertile women with untreated inactive tuberculosis lesions visible on chest imaging who are planning to undergo IVF-ET. All patients underwent IGRA testing. Baseline characteristics, such as age, body mass index (BMI), infertility factors, ultrasound follicle count, and hormone levels, were collected. Pregnancy outcomes, including live birth rates, oocyte retrieval numbers, embryo quality, clinical pregnancy, miscarriage, and preterm birth rates, were followed and compared between the IGRA-positive and IGRA-negative groups.ResultsAmong 836 patients, the IGRA positivity rate was 42.5%. The cumulative miscarriage rate was higher in the IGRA-positive group than in the IGRA-negative group (21.5% vs. 15.0%, p = 0.047). No significant differences were found in clinical pregnancy or live birth rates. Age, BMI, and endometrial thickness were independent risk factors influencing clinical pregnancy and live birth rates, while the IGRA status was not.ConclusionIn infertile women with untreated inactive tuberculosis lesions on chest radiography, IGRA positivity is associated with higher cumulative miscarriage rates following IVF-ET. Early IGRA screening and intervention may help improve pregnancy outcomes.